Development of a sensitive method for the determination of oxycodone and its major metabolites noroxycodone and oxymorphone in human plasma by liquid chromatography–tandem mass spectrometry - Gaudette, Fleur; Sirhan-Daneau, Andréa; St-Onge, Maude; Turgeon, Jacques; Michaud, Veronique (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2016)
•Our HPLC–MS/MS assay is accurate, robust and highly selective.•The limit of detection of 30pg/mL for all analytes.•Analytical method suitable to conduct PK studies using a small single dose of OXY.•Our assay permits a proper characterization of half-life.•Our assay would determine precisely PK parameters in CYP2D6 EM and PM subpopulations. Oxycodone is an opioid agonist largely prescribed for the treatment of moderate to severe pain. Variability in analgesic efficacy could be explained by inter-subject variations in plasma levels of parent drug and its active metabolite, oxymorphone. For this purpose it is necessary to develop and validate a sensitive and selective analytical method for the quantification of oxycodone and its major metabolites, noroxycodone and oxymorphone, in human plasma. The analytical method consisted of a liquid–liquid extraction procedure followed by a high performance liquid chromatography with heated assisted electrospray ionization mass spectrometry (HPLC–HESI–MS/MS). The chromatographic separation was achieved using gradient elution with a mobile phase consisting of ethanol and 10mM ammonium acetate on a Synergi MAX-RP analytical column (150×2mm, 4μm) protected by a security guard cartridge (C12 4×2mm) at a flow rate of 300μL/min.The calibration functions are linear in the range of 300–50,000pg/mL for oxycodone and noroxycodone and 50 to 10 000pg/mL for oxymorphone. Intra- and inter-day relative standard deviations are less than 5.5% and 6.4%, respectively for all analytes. The limit of detection was 30pg/mL for all analytes. We introduce a new HPLC–HESI–MS/MS sensitive and specific analytical method capable to simultaneously quantify oxycodone, noroxycodone and oxymorphone, in human plasma, and suitable for the conduct of pharmacokinetic studies after a single dose administration of the parent compound.